DIGERAKKAN OLEH KASIH KRISTUS: KHARISMA DAN SPIRITUALITAS SANTO VINSENSIUS DALAM KARYA PENDIDIKAN KONGREGASI MISI - Widiatna, Alexius Dwi (Lembaga Penelitian STKIP Widya Yuwana, 2024)
The purpose of this study is to explore the charism and spirituality of Saint Vincent de Paul to be implemented in teaching and learning in schools. Saint Vincent was moved by the love of God to love Him through the service to poor. Loving God and loving others who are poor and suffering are an inseparable unity. Saint Vincent's spirituality must also animate his followers in educational work. Vincentian schools educate students to love the poor. The researcher explores the charism and spirituality of Saint Vincent and its implementation in educational work. Through observations, interviews and focus group discussions among the coaches, supervisors, administrators of the Lazaris Foundation, the researchers concluded that the main values ​​(core values) that are fostered in Vincentian schools are compassion, competence, and Vincentian virtues. It is expected that this research would be a meaningful reference for the relevant researchers, stakeholders, and educational practitioner who wants to implement vincentian values in teaching and learning process in schools.